Assessing the impacts of non-tariff measures on the export of Vietnam’s main agricultural and seafood products - Nga, Le Thi Viet; Minh, Doan Nguyen; Cong, Phan The (International Journal of Innovative Research and Scientific Studies, 2023)
With the development of free trade agreements, tariff barriers are gradually removed, and non-tariff measures are playing an important role in the trade policies of countries. However, studies on the effects of non-tariff measures on trade show a great disparity in results and both negative and positive influences can be found when non-tariff measures are imposed in different contexts. The heterogeneity in the result is often hypothesized to be the consequence of intrinsic characteristics related to products and countries; therefore, arguably, unbiased and reliable estimation of non-tariff measure effect on trade should be analyzed in product level data for a specific country. Hence, the study attempts to use the gravity model and Poisson Pseudo-Maximum Likelihood estimation (PPML) to quantify the effects of non-tariff measures on the export of some agricultural and seafood products of Vietnam to certain main markets including the United States (US), European Union (EU), China, and Japan. The research findings show that from a national perspective, non-tariff measures mostly have a negative impact on agricultural exports, especially sanitary and phytosanitary measures (SPM), and countervailing measures (CM). In terms of commodities, coffee and seafood are particularly sensitive to non-tariff measures, while other key agricultural product groups are mostly affected by tariff measures.